Beginning ASP.NET 4.5.1 in C# and VB - Spaanjaars, Imar (John Wiley & Sons, 2014)
Provides a firm foundation for coders new to ASP.NET and key insights for those not yet familiar with the updates in the 4.5.1 release. Guides you through the process of creating a fully functional, database-driven website, from creation to the successful deployment of the website to a production environment